An Electronic Barrel Bung to Wirelessly Monitor the Biological Aging Process of Fino Sherry Wine - Juan J. Sanchez-Gil; Eduardo Canete-Carmona; Maria Brox; Andres Gersnoviez; Miguel Angel Molina-Espinosa; Juan C. Gamez-Granados; Juan Moreno (IEEE Access)
Wine aging is a fundamental stage in the creation of special high-quality wines, such as sherries and similar wines. To undergo the process of “biological aging”, some of these wines are stored in oak casks for long periods. During this process, a thin layer of yeast is spontaneously formed on the surface of the wine. This layer protects the wine from oxidation and contributes to its unique organoleptic characteristics. This work presents the prototype of an instrumented bung capable of monitoring, in real-time, the absorbance evolution of the Fino Sherry wine during its biological aging process. The results of the tests carried out in the laboratory showed that the device can directly measure the absorbance at wavelengths of 420 nm and 520 nm, detecting small changes produced by the wine oxidation processes. This work has significant implications for winery technicians and oenologists as they could analyze the evolution of the wine in real time, detect problems in advance, and avoid work-related accidents. These conclusions solidify the enduring relevance of this research and offer a robust foundation for future developments in the field.